Are Portuguese population exposed to Zearalenone? A human biomonitoring study as a contribution to the risk assessment of an endocrine disruptor - Martins, Carla (2019)
Zearalenone (ZEN) is a mycotoxin that occurs widely in food commodities with particular incidence in cereals. Due to chemical structures similar to the endogenous oestrogen 17-β-estradiol, ZEN and its metabolites exert estrogenic toxicity. Therefore, it is crucial to assess ZEN exposure among the population and biomarker-driven research is a promising method to assess the human exposure. For this reason, ZEN metabolites such as α-zearalenol (α-ZEL), β-zearalenol (β-ZEL), α-zearalenal (α-ZAL), β-zearalenal (β-ZAL), zearalanone (ZAN) (phase I) and the glucuronides ZEN14GlcA, α-ZEL14GlcA and β-ZEL14Glc (phase II) were identified in biological fluids. With a potency factor of 60 relative to ZEN, α-ZEL is the most relevant metabolite in terms of human health. ZEN is characterized by a fast metabolism and excretion, therefore urine is the matrix commonly used to assess the exposure to this mycotoxin and its metabolites. To date, in Portugal, there is a lack of human studies to assess biomarkers of exposure to ZEN. Within the Scope of National Food, Nutrition, and Physical Activity Survey of the Portuguese General Population (2015-2016), 24h-urine samples and non-consecutive dietary assessments (two 24-hour recalls, 8-15 days apart) from 94 participants were included in the present study. Following a salt-assisted matrix extraction, urine samples were analyzed using LC-MS/MS for the simultaneous determination of ZEN, α-ZEL, β-ZEL, α-ZAL, β-ZAL, ZAN and ZEN14GlcA. ZEN and ZEN-14-GlcA were detected in 52% (36/69) and 14% (10/69) of the analyzed samples, with a mean concentration of 1.2 and 6.9 µg/L, respectively. The metabolites α-ZEL, β-ZEL, α-ZAL, β-ZAL, ZAN were not detected in the urine samples. Considering the 24h-urinary volume, the mean dietary excretion of ZEN and ZEN-14-GlcA was 1.5 and 7.8 µg/day, respectively. These data will allow the determination of Probably Daily Intake of zearalenone with more accuracy since it reflects the internal exposure of participants.